FAMILY CLIMATE, PERCEPTION, AND ADOLESCENTS' STRESS PRIOR TO AND DURING COVID-19 PANDEMIC - Indah Dahlia; Dwi Hastuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
The COVID-19 pandemic has various impacts on life, one of which causes stress in adolescents. This study aims to analyze the influence of family climate and adolescent perceptions of stress levels during the pandemic. This study used a cross-sectional study design. The sampling in this study used a non-probability sampling method with a voluntary sampling technique through the distribution of bold questionnaires. The research sample was 113 junior high and high school students aged 13-18 in the Greater Jakarta area (Jakarta, Bogor, Depok, Tangerang, Bekasi). Based on the study results, the category of almost all teenagers has a family climate in the medium. Almost approaching adolescents, adolescents' perceptions and stress levels during the pandemic are included in the low category. There was no significant difference between adolescents' perceptions before and during the pandemic, while adolescents' stress level was significantly higher than before the pandemic. The study's results showed that family climate was negatively related to adolescent stress levels during the pandemic. On the other hand, adolescent perceptions during the pandemic were significantly positively related to the stress level of adolescents during the pandemic. Factors that significantly negatively affect adolescent stress levels during the pandemic are family size and family climate (on the dimensions of relationships in the family and family violence). Adolescent perceptions during the pandemic have a positive effect on adolescent stress levels during the pandemic.